A common genetic variant of fucosyltransferase 2 correlates with serum carcinoembryonic antigen levels and affects cancer screening in patients with primary sclerosing cholangitis. Issue 1 (1st February 2016) - Wannhoff, Andreas; Folseraas, Trine; Brune, Maik; Rupp, Christian; Friedrich, Kilian; Knierim, Johannes; Weiss, Karl Heinz; Sauer, Peter; Flechtenmacher, Christa; Schirmacher, Peter; Stremmel, Wolfgang; Hov, Johannes R; et al.
Abstract : Background: Primary sclerosing cholangitis (PSC) patients are at increased risk of biliary tract cancer, and carcinoembryonic antigen (CEA) serum levels might be used for screening. Objective: To examine cancer screening with CEA in PSC patients and analyse how serum CEA levels are affected by genetic variants of fucosyltransferase ( FUT ) 2 and 3 . Methods: In a retrospective cohort analysis we evaluated CEA levels in 226 PSC patients, including 19 with biliary malignancy, and investigated how FUT2 and FUT3 SNPs affected CEA levels. Receiver‐operating‐characteristic (ROC) analysis was performed and cut‐off values were determined based on Youden's index. A control cohort contained 240 patients, including 28 with biliary malignancy. Results: Median CEA concentration was lower in cancer‐free patients (1.4 ng/mL) than in cancer patients (2.0 ng/mL, P  = 0.014). ROC analysis revealed an area under the curve (AUC) of 0.671, the optimal cut‐off was 3.2 ng/mL. The FUT2 variant rs601338 (G428A) correlated with CEA levels, and the effect was most prominent in a subgroup of patients genetically incapable of expressing CA19‐9. The AUC improved if ROC analysis was performed separately for wild‐type (AUC: 0.731) and homozygous mutant (AUC: 0.816) G428A. The influence of FUT2 on CEA was confirmed in the control cohort. Conclusions: CEA is interesting for biliary‐malignancy screening in PSC patients, especially in patients who do not express CA19‐9. This is the first study to show that the combined use of CEA measurement and FUT genotyping is clinically beneficial and that it might enhance the early detection of biliary malignancy in clinical practice. This approach could also be effective when screening for other common gastrointestinal malignancies.